2016
DOI: 10.1007/s00418-016-1527-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of the YIPF protein family in mammalian cells

Abstract: In this study, we carry out a systematic characterisation of the YIPF family of proteins with respect to their subcellular localisation profile, membrane topology and functional effects on the endomembrane system. YIPF proteins primarily localise to the Golgi complex and can be grouped into trans-Golgi-localising YIPFs (YIPF1 and YIPF2) and cis-Golgi-localising YIPFs (YIPF3, YIPF4 and YIPF5), with YIPF6 and YIPF7 showing a broader profile being distributed throughout the Golgi stack. YIPF proteins have a long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Confocal imaging showed that YIPF6 localized to the ER and Golgi in mouse hepatocytes, based on colocalization with the ER marker protein calnexin and cis-Golgi matrix protein GM130 (SI Appendix, Fig. S5B), consistent with previous reports (37,38). We studied ER and Golgi fractions to determine the subcellular distribution of FGF21.…”
Section: Increased Hepatic Secretion Of Fgf21 Mediates Protective Effsupporting
confidence: 85%
“…Confocal imaging showed that YIPF6 localized to the ER and Golgi in mouse hepatocytes, based on colocalization with the ER marker protein calnexin and cis-Golgi matrix protein GM130 (SI Appendix, Fig. S5B), consistent with previous reports (37,38). We studied ER and Golgi fractions to determine the subcellular distribution of FGF21.…”
Section: Increased Hepatic Secretion Of Fgf21 Mediates Protective Effsupporting
confidence: 85%
“…YIPF5 is a 5-span transmembrane protein ( Figure 1B) that cycles between the ER and the Golgi and localizes at ER exit sites, the ER-Golgi intermediate compartment, and part of the cis-Golgi (30)(31)(32)(33). Previous studies in HeLa cells have suggested that YIPF5 plays a role in cargo exit from the ER (34), resulting in protein overload, thereby triggering the ER stress response.…”
Section: The Journal Of Clinical Investigation R E S E a R C H A R T mentioning
confidence: 98%
“…cells. YIPF2 belongs to YIP family which has been reported to interact with RAB small G protein and plays vital roles in intracellular vesicular transport 20,22,24,31,37 . Numerous reports have discovered that some chemotherapeutic agents including PEM can induce endoplasmic reticulum (ER) stress in tumor cells 12,38 .…”
Section: Discussionmentioning
confidence: 99%
“…YIPF2 belongs to the YIP protein family, which has been reported to bind to RAB proteins to regulate vesicular transport 22,31 . Thus, we performed co-immunoprecipitation (co-IP) assays to investigate why YIPF2 increased the surface expression of TNFRSF10B.…”
Section: Yipf2 Inhibits the Interaction Between Tnfrsf10b And Rab8mentioning
confidence: 99%